Improved responses to elevated CO2 in durum wheat at a low nitrate supply associated with the upregulation of photosynthetic genes and the activation of nitrate assimilation. (July 2017) - Vicente, Rubén; Pérez, Pilar; Martínez-Carrasco, Rafael; Morcuende, Rosa
Highlights: Little change in Vc, max with elevated CO2 at low N, but a decrease at high N. Nitrate-dependent elevated-CO2 response of nitrate reductase at early grain filling. CO2 acclimation of photosynthesis at high N related to photosynthesis and N assimilation gene repression. Major role of whole-plant N assimilation in durum wheat response to elevated CO2 . Abstract: Elevated CO2 often leads to photosynthetic acclimation, and N availability may alter this response. We investigated whether the coordination of shoot-root N assimilation by elevated CO2 may help to optimize the whole-plant N allocation and maximize photosynthesis in hydroponically-grown durum wheat at two NO3 − supplies in interaction with plant development. Transcriptional and biochemical analyses were performed on flag leaves and roots. At anthesis, the improved photosynthetic acclimation response to elevated CO2 at low N was associated with increased Rubisco, chlorophyll and amino acid contents, and upregulation of genes related to their biosynthesis, light reactions and Calvin-Benson cycle, while a decrease was recorded at high N. Despite the decrease in carbohydrates with elevated CO2 at low N and the increase at high N, a stronger upward trend in leaf NR activity was found at low rather than high N. The induction of N recycling-related genes was accompanied by an amino acids decline at high N. At the grain-filling stage, the photosynthetic acclimation to elevated CO2 at high N was associated with the downregulation of both N assimilation, mainly in roots, and photosynthetic genes. At low N, enhanced root N assimilation partly compensated for slower shoot N assimilation and maximized photosynthetic capacity.